2020
DOI: 10.1177/1358863x20977678
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study evaluating hospitalization rates for chronic limb-threatening ischemia during the COVID-19 outbreak in Campania, Italy

Abstract: The expansion of coronavirus disease 2019 (COVID-19) prompted measures of disease containment by the Italian government with a national lockdown on March 9, 2020. The purpose of this study is to evaluate the rate of hospitalization and mode of in-hospital treatment of patients with chronic limb-threatening ischemia (CLTI) before and during lockdown in the Campania region of Italy. The study population includes all patients with CLTI hospitalized in Campania over a 10-week period: 5 weeks before and 5 weeks dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 12 publications
(16 reference statements)
3
20
0
5
Order By: Relevance
“…Stabile and colleagues report that, during lockdown in Italy, hospital admissions for CLI decreased by 66% and the rate of amputation among hospitalized patients increased dramatically after lockdown restrictions were eased. 7 These results are consistent with delayed care and subsequent presentation of more advanced disease, which was not salvageable in many cases. Clearly, COVID-19 has had significant impact on the outcomes of patients with CLI who are dependent on the availability and coordination of multiple medical/surgical specialists.…”
supporting
confidence: 65%
“…Stabile and colleagues report that, during lockdown in Italy, hospital admissions for CLI decreased by 66% and the rate of amputation among hospitalized patients increased dramatically after lockdown restrictions were eased. 7 These results are consistent with delayed care and subsequent presentation of more advanced disease, which was not salvageable in many cases. Clearly, COVID-19 has had significant impact on the outcomes of patients with CLI who are dependent on the availability and coordination of multiple medical/surgical specialists.…”
supporting
confidence: 65%
“…These factors may all have disproportionately affected minority groups and elderly patients, who are at greatest risk from SARS‐CoV‐2. An Italian study of CLTI patients also found that patients may be gun‐shy in reporting symptoms for fear of SARS‐CoV‐2 exposure at hospital admission—also confirmed for patients with acute coronary syndromes 30 . Thus, patients' fear is very real.…”
Section: Resultsmentioning
confidence: 82%
“…A limitation of our data is the lack of data on severity. Patients presenting with critical ischemia often have co-morbidities, consulting at already advanced stages of the disease, and the stages on arrival were potentially more severe [14,15]. The drop in the number of diagnoses of these pathologies is likely related to inadequate patient management (through changes in patient behavior and hospital organization), rather than to a real decrease in their incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and associated long-term lockdown have led to a severe treatment gap due to the effects on medical practices, the organization of hospital care, as well as in the behavior of patients and clinicians. In developed countries, a significant decrease in emergency room visits [1], surgical emergencies [8], cardiac interventional activity and management of acute coronary syndromes [9][10][11][12] and other emergency vascular activities [13][14][15] has been clearly demonstrated. However, most data were collected during the lockdown period without sufficient follow-up regarding data ascertainment, thus, raising the problem of incomplete data.…”
Section: Introductionmentioning
confidence: 99%